The role of digital personal photography: a theoretical exploration with Deleuze-Guattari approach - Sun, Zhen (Lumina, 2020)
The innovations of digital photography are transforming people’s experiences of producing, manipulating, sharing, and using their personal photographic images. The essentialist and representational dualistic viewpoints of photography that were initially developed in the era of the Daguerreotype appear no longer tenable in the contemporary photography era. This study focuses on the ever-changing role of personal photographic images in the three typical photography events, i.e., the selfie production, the real-time beautified video sharing on the social media, and the production of deepfake AI face-swaps. The study is inspired by the Deleuze-Guattari’s conceptual framework that is mainly composed of the concepts of minor literature, assemblage, becoming, and de/re-territorialization, and defines personal photographic images as both an assemblage and a constitutive part of larger assemblages, i.e., personal photograph production and usage events. The tetravalent model of assemblages is used as a major analysis toolkit to achieve the research purpose. A thorough analysis and discussion shows the material and expressive components that compose different sizes of assemblages and the emergent capacities. It also discloses how digital photography apps play as a line of flight to de/re-territorialize the presumed representational association between individuals and their photographic images. The images have become one of the multiplicities or becoming of individuals, either interacting with individuals, acting on individuals, or extending individuals’ disembodied experiences. This study seeks to develop alternative theoretical lenses on the role of digital personal photography in everyday life and the rhizomatic experiences that it generates.